Nanoplatform Self‐Assembly from Small Molecules of Porphyrin Derivatives for NIR‐II Fluorescence Imaging Guided Photothermal‐Immunotherapy. Issue 11 (18th February 2022) - Cao, Yanbing; Wei, De; Yang, Lixia; Luo, Zijin; Yu, Peiwen; Li, Hao; Zhang, Cao; Liu, Xiaolong; Wu, Fengshou; Wu, Ming; Zeng, Yongyi
Abstract: Combinatorial photothermal and immunotherapy have demonstrated great potential to remove primary tumors, suppress metastases, and prevent tumor recurrence. However, this strategy still confronts patients with many limitations, such as complex components, sophisticated construction, and inadequate therapeutic efficacy. In this work, small molecules of porphyrin derivatives (PPor) which can self‐assemble into monodispersed nanoparticles without supplement of any other ingredients or surfactants are developed. The formed PPor nanoparticles (PPor NPs) exhibit highly photothermal conversion efficiency of 70% and NIR‐II luminous abilities originate from the strong intramolecular charge transfer (ICT) effect of D‐A structure under 808 nm laser irradiation, thus achieving NIR‐II fluorescence imaging guided photothermal therapy (PTT) against primary tumors with a high cure rate. More importantly, tumor‐associated antigens (TAAs), together with damage‐associated molecular patterns (DAMPs) released from PTT‐treated cancer cells, are proved to elicit immune responses to some degree. After combination with programmed cell death‐1 (PD‐1) antibodies, a robust systematic antitumor immunity is generated to restrain both primary and abscopal tumors growth, prolong survival, and prevent pulmonary metastasis on an aggressive 4T1 murine breast tumor model. Thus, this study provides a promising therapeutic paradigm with porphyrin derivatives nano‐assembly as phototheranostic agents for the treatment of aggressive tumors with high efficiency. Abstract : A new small‐molecule dye (PPor) based on porphyrin derivatives is developed which can self‐assemble into monodispersed nanoparticles without supplement of any other ingredients or surfactants, with the ability of excellent NIR‐I absorption and NIR‐II fluorescence emission for image‐guided photothermal‐immunotherapy to restrain tumors growth and prevent pulmonary metastasis.